Fleet assignment and planning for an airline using integer linear programming - Yusuf, Akbar; Techapun Raengkhum; Pakorn Adulbhan; Sharif, M. N.; Government of Canada (Bangkok : Asian Institute of Technology, 1977)
This study concerns the cost minimization of an Airline's operations over a planning horizon of four years. The study is made for Pakistan International Airlines (PIA) which operates both on domestic and international routes a The Airline operates a fleet consisting of different types of aircrafts. If the fleet size is known or fixed in advance, the cost of operation is minimized with the help of an optimal allocation of various aircraft types to fly on various routes in each period, where period is one calendar year. If the fleet size can be made variable, the fixed or holding costs can also be minimized by holding an optimal (minimal) fleet in each period. Thus the total fixed cost and cost of operation are minimized by an optimal (minimal) fleet in each period and a simultaneous decision on an optimal allocation of various aircraft types to fly on various routes in each period. An estimation of the number of passengers likely to travel along various routes over the planning horizon and data for the operational and fixed costs of each aircraft type were provided by the airline. Integer linear programming models are used to minimize the costs in the light of demand, operational, budgetary, feasibility and availability constraints.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1977
Keywords: Air lines -- Management -- Mathematical models